The Impact of Self-Relevance on Preschool Children’s Sharing - Zhang, Wenjie; Xiang, Songmei; Dai, Hongmei; Ren, Mengmeng; Shen, Yuqi; Fan, Wei; Zhong, Yiping (Frontiers in Psychology, 2019)
This study was designed to investigate the impact of self-relevance between preschool children and recipients on children’s sharing behavior in dictator games using a forced-choice resource distribution paradigm. Experiment 1: A total of 75 children aged 3-6 years were evaluated in a first-party situation in which they were distributed as recipients and dictators and shared resources with distracting recipients with different extents of self-relevance under three different payoff structures, including non-costly, costly and envy structures. Children could choose between a sharing option and a non-sharing option. The results showed that, in a first-party situation, children aged 3-6 years old typically share more resources with highly self-relevant recipients (friends) than with moderately self-relevant recipients (acquaintances) and lowly self-relevant recipients (strangers) and that they share more resources with moderately self-relevant recipients (acquaintances) than lowly self-relevant recipients (strangers). Experiment 2: A total of 62 children aged 3-6 years old were evaluated in a third-party situation in which they were distributed not as recipients but only dictators, making decisions between the options of sharing more or sharing less with distracting recipients who had different extents of self-relevance under three different payoff structures, such as non-bias, high self-bias and low self-bias. The results showed that, in a third-party situation, children typically share in a similar manner to that of Experiment 1, meaning that children display selective generosity and that the self-relevance between the children and recipients played a key role. Across age groups, this study of preschool children (total N = 137) demonstrates a degree of effect of self-relevance on preschool children’s sharing in first-party and third-party situations, with highly self-relevant recipients receiving a more preferential share in the dictator game than those with low self-relevance, although this effect was stronger in the older preschool children.